Protective Effect Against Toxoplasmosis in BALB/c Mice Vaccinated With Toxoplasma gondii Macrophage Migration Inhibitory Factor - Liu, Kang; Wen, Hongyang; Cai, Haijian; Wu, Minmin; An, Ran; Chu, Deyong; Yu, Li; Shen, Jilong; Chen, Lijian; Du, Jian (Frontiers in Microbiology, 2019)
Toxoplasma gondii is an obligate intracellular parasite responsible for toxoplasmosis, which can cause severe disease in the fetus and immunocompromised individuals. Developing an effective vaccine is crucial to control this disease. Macrophage migration inhibitory factor (MIF) has gained substantial attention as a pivotal upstream cytokine to mediate innate and adaptive immune responses. Homologues of MIF have been discovered in many parasitic species, and one homologue of MIF has been isolated from the parasite Toxoplasma gondii. In this study, the recombinant Toxoplasma gondii MIF (rTgMIF) as a protein vaccine was expressed and evaluated by intramuscular injection in BALB/c mice. We divided the mice into different dose groups of vaccines, and all immunizations with purified rTgMIF protein were performed at 0, 2, and 4 weeks. The protective efficacy of vaccination was analyzed by antibody assays, cytokine measurements and lymphoproliferative assays, respectively. The results obtained indicated that the rTgMIF vaccine elicited strong humoral and cellular immune responses with high levels of IgG antibody and IFN-γ production compared to those of the controls, in addition to slight higher levels of IL-4 production. After vaccination, a stronger lymphoproliferative response was also noted. Additionally, the survival time of mice immunized with rTgMIF was longer than that of the mice in control groups after challenge infection with virulent T. gondii RH tachyzoites. Moreover, the number of brain tissue cysts in vaccinated mice was reduced by 62.26% compared with the control group. These findings demonstrated that recombinant TgMIF protein is a potential candidate for vaccine development against toxoplasmosis.